Legal Recourse and the Demand for Auditing. - Wallin, David E. (The Accounting Review, 1992)
Investigates the demand for auditing in environments both with and without legal recourse. Important role of accounting information in a decentralized economy; Review of related literature; Results showing that there is a demand for disclosure in auditing regardless of whether legal recourse was present.